MUSYAWARAH (SYŪRĀ) DALAM KETATANEGARAAN ISLAM PRESPEKTIF HADIST TEMATIK - Muhammad Panji Islami; Muhammad Alif (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
Consultation (syūrā) is a key tenet of Islamic governance that is highly stressed in the Qur’an and the actions of the Prophet Muhammad, as indicated in numerous hadiths. Nevertheless, the comprehension of syūrā within Islamic constitutional discourse is frequently addressed from a normative perspective and seldom analyzed through a thematic hadith lens. This article seeks to examine the notion of consultation (syūrā) through the lens of hadith by investigating its types, foundational principles, and consequences for Islamic governance utilizing a thematic hadith approach. This research utilizes a qualitative methodology, with library research as its main technique. Data were gathered from prominent hadith collections by thematically identifying keywords linked to consultation, deliberation, and leadership, and were examined using classification and contextual interpretation methods. The results show that syūrā in the hadiths manifests in various ways, such as consultative decision-making, group discussions, and the participation of capable individuals in public matters. Moreover, the hadiths highlight the ethical principles of syūrā, including justice, transparency, mutual respect, and accountability in decision-making. Regarding its effects, the practice of consultation aids in political stability, fosters public trust, and promotes collective well-being in Islamic governance. Thus, syūrā, when viewed through the lens of thematic hadith, embodies a fundamental aspect of Islamic constitutional ethics and acts as a normative basis for participatory governance in modern Islamic political theory.